Theoretical review of the emotional management of children with special education needs with visual impairment - Magiman, Mohamad Maulana; Nordin, Mohd Norazmi; Qi, Wan Mei; Baharudin, Siti Mastura; Yusoff, Imran; Abbas, Mohd Saleh; Mustafa, Mohamad Zaid (African Science Publications, 2024)
To get a clearer picture of emotions in MBPK, the researcher looked at this aspect in terms of theories closely related to emotions. The theory is basically a description of a phenomenon and the interaction of its variables that are used to try to explain or predict. In other words, theory allows other people involved in a field, especially researchers, to recognize core concepts and continue to explore that field. The main theories about emotions can be divided into three categories, namely physiological theories, neurological theories, and cognitive theories. These three categories discuss the connection between body, brain, and emotional response from different perspectives. Among them, the theory of physiological emotions represented by the James-Lange Theory of Emotions suggests that emotions occur as a result of a physiological response to an event that external stimuli will lead to a physical response while emotions are shown based on the interpretation of physical responses the said. For example, when a MBPKP person is not given something they want, the student starts crying or screaming on the floor and the body feels hotter, then sums up that he is experiencing angry or sad emotions. In other words, being angry or sad is the result of a physical reaction that is screaming and crying. However, the exact emotion may be less distinguishable especially for MBPKP if based on this theoretical proposal.